Risk for developing eating disorders in adults diagnosed with attention deficit hyperactivity disorder: An integrative literature review (Research, Society and Development, 2025)
Objective: to investigate whether adults with ADHD are at risk of developing eating disorders or worsening their clinical condition. Methodology: a six-step methodology was used, including searches in PubMed and LILACS databases and selection of articles in English or Portuguese published between 2015 and 2025. After defining the inclusion and exclusion criteria, the final sample included eight studies, assessed using a structured instrument that included methodological data, outcomes, and level of evidence. Results: the findings showed a significant association between ADHD and eating disorders: adults with ADHD have up to a fourfold increased risk of developing binge eating and bulimia nervosa. In a twin study, 91% of the covariance between ADHD and binge eating was attributed to shared genetic factors. Impulsivity, dysfunction in emotional regulation, and altered reward circuitry emerge as central mechanisms of this relationship. Even after adjusting for psychiatric comorbidities, the association between ADHD and bulimia remained significant, especially in obese women. Conclusion: adults with ADHD have a higher prevalence of eating disorders, with impulsivity and emotional dysregulation as key factors. Further longitudinal studies and specific clinical care are recommended, promoting comprehensive management involving mental health and nutrition.